2016
DOI: 10.5603/cj.a2016.0008
|View full text |Cite
|
Sign up to set email alerts
|

Association between aortic stiffness and left ventricular function in inflammatory bowel disease

Abstract: (Cardiol J 2016; 23, 2: 202-210)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…2, Panel BeC). It is known that increased arterial stiffness leads to an early return of the reflected waves and augmentation of late systolic pressure, increased workload of the left ventricle and left ventricular hypertrophy [6]. Whether arterial stiffening is associated with eccentric or concentric left ventricular hypertrophy in patients with MetS is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, Panel BeC). It is known that increased arterial stiffness leads to an early return of the reflected waves and augmentation of late systolic pressure, increased workload of the left ventricle and left ventricular hypertrophy [6]. Whether arterial stiffening is associated with eccentric or concentric left ventricular hypertrophy in patients with MetS is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…We previously suggested that at least a part of the cardiovascular risk reported in patients with chronic inflammation could be mediated by an increase in aortic stiffness [3]. Aortic stiffness and reflected waves are increased in patients with chronic high-grade inflammation [4,5] and associated with left ventricular function [6]. An increase in aortic stiffness has been also reported in patients with MetS [7,8].…”
Section: Introductionmentioning
confidence: 97%
“…We previously proposed that this apparent contradiction, reported as “inflammatory bowel disease paradox,” could be at least in part explained by the chronic inflammation and consequent arterial stiffening . In this regard, a significant relationship between aortic stiffness and left ventricular systolic and diastolic dysfunction in patients with IBD has recently been reported . Here, we aimed to perform an individual participant data (IPD) meta‐analysis to determine whether patients with IBD have an increased aPWV after adjustment for major confounders, and to test whether inflammation is associated with aortic stiffening in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanotic patients with congenital heart diseases are often characterized by increased arterial stiffness in comparison with healthy population 2 . There is a direct relationship between aortic stiffness and left ventricular systolic and diastolic dysfunction in patients with inflammatory bowel disease 3 . Eradication of hepatitis C virus infection causes a significant decline in liver stiffness -particularly in patients with high baseline level of inflammation or patients who received direct-acting antiviral agents 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%